Work-family conflict and its related factors among emergency department physicians in China: A national cross-sectional study - Yan, Shijiao; Li, Changjun; Zhang, Jiali; Wu, Yafei; Tian, Mengge; Liu, Li; Zhou, Xuan; Zheng, Jianwei; Jiang, Nan (Frontiers in Public Health, 2023)
Background Work-family conflict is common among emergency department physicians. Identifying the factors associated with work-family conflict is key to reducing its negative impact on mental health and work attitudes. However, the work-family conflict of Chinese emergency department physicians and the related factors have been scarcely studied. Objective This study aimed to investigate the current status and related factors of work-family conflict among Chinese emergency department physicians. Methods A national cross-sectional study was conducted among emergency department physicians in China from June 2018 to August 2018. A standard questionnaire was used to investigate the demographic characteristics, work-related factors, and work-family conflict of emergency department physicians. The generalized linear regression analysis was used to identify the related factors of work-family conflict. Results A total of 10,457 licensed emergency department physicians participated in the study. The average score of work-family conflict among the enrolled emergency department physicians was 19.27 ± 3.94, and the prevalence of high levels of work-family conflict was 69.19%. The multivariable regression analysis showed that emergency physicians who were female (linear regression coefficient, −0.25; SE, 0.08; P = 0.002), older than 40 years (linear regression coefficient,−0.53; SE, 0.14; P < 0.001), and earning more than 4,000 CNY per month (e.g., 4,001 6,000 vs. ≤4,000 CNY: linear regression coefficient, −0.17; SE, 0.09; P = 0.04) had lower work-family conflicts. However, emergency department physicians who were married (linear regression coefficient, 0.37; SE, 0.11; P < 0.001), highly educated (linear regression coefficient, 0.46; SE, 0.10; P < 0.001), had a high technical title (e.g., intermediate vs. junior technical title: linear regression coefficient, 0.61; SE, 0.09; P < 0.001), worked in a high-grade hospital (e.g., tertiary hospital vs. emergency center: linear regression coefficient, 0.38; SE, 0.11; P < 0.001), had a higher frequency of night shifts (e.g., 6 10 night shifts per month vs. 0 5 night shifts per month: linear regression coefficient, 0.43; SE, 0.10; P < 0.001), self-perceived shortage of physicians in the department (linear regression coefficient, 2.22; SE, 0.08; P < 0.001), and experienced verbal abuse (linear regression coefficient, 1.48; SE, 0.10; P < 0.001) and physical violence (linear regression coefficient, 0.84; SE, 0.08; P < 0.001) in the workplace had higher work-family conflict scores. Conclusion Most emergency department physicians in China experience a high-level work-family conflict. Hospital administrations are recommended to develop family-friendly workplace policies, establish a scientific shift system, and keep the number of emergency department physicians to meet the demand to reduce work-family conflict.